THE EFFECT OF STRATIFIED DOSES OF CURRY LEAF EXTRACT (MURRAYA KOENIGII) ON TOTAL CHOLESTEROL AND TRIGLYCERIDES IN MALE SPRAGUE-DAWLEY RATS INDUCED BY HIGH FAT FEED - Muhammad Iqbal Reynaldi; Santoso Santoso; Kusmiyati Tjahjono (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: High level of total cholesterol and tryglicerides in the blood can cause atherosclerosis. Curry leaves are often used by the society to reduce total cholesterol and trygliceride levels in the blood, but no studies have examinded the effective dosage of curry leaf extract to reduce total cholesterol and triglyceride levels.Aim: This study aims to determine the effect of giving curry leaf extract (Murraya koenigii) on cholesterol and triglyceride levels of male Sprague-Dawley rats induced by high fat feed.Methods: This study was a true experimental study with a pre-post test with randomized control group design. The subjects of the study were male Sprague-Dawley rats induced by high fat feed for 10 days. Cholesterol and triglyceride levels were measured by enymatic methods. Then, the data were analyzed using paired t test and for P3 group total cholesterol using the Wilcoxon test to analyze the differences in total cholesterol and triglyceride levels between before and after given the curry leaf extract, Repeated Anova test to analyzed the differences between groups which was then followed by post hoc bonferoni and One Way Anova to analyze the differences in total cholesterol and triglyceride levels between groups.Results: There was no significant differences in total cholesterol levels between before and after given the curry leaf extract at a dose of 200 mg/KgBW, 300 mg/KgBW, and 400 mg/KgBW (p= 0.641 for the P1 group, p= 0.385 for the P2 group and p= 0.398 for the P3 group). In contrast to triglyceride levels, there were differences in triglyceride levels before and after administration of curry leaf extrcat at a a dose of 300 mg/KgBW (p= 0.012), while the other groups were not significant.Conclusion: The stratified doses of curry leaf extract (Murraya koenigii) in this study could not reduce cholesterol level and triglyceride levelKeywords: Curry leaf extract; Dyslipidemia; Total Cholesterol; Triglyceride